Persistent current joints between NbTi superconducting wires - Brittles, G (2016)
Persistent current joints are critical components of superconducting magnets, and improvements in their properties are key to the production of next generation devices. Despite having been made routinely for more than half a century, the science underpinning the performance of joints between NbTi wires remains poorly understood. At this critical juncture, where new jointing methods are being sought for NbTi, it is essential that we develop a sound understanding of the factors in uencing joint quality. The aim of this thesis was to identify the characteristic microstructural and superconducting properties of joints produced by the three standard jointing methods for NbTi: soldering, spot welding and cold pressing. There were three main components to this work. The first was to obtain a complete characterisation of Jc(B, T) and Bc2(T) for the raw materials from which the joints were made, which was done by standard magnetic methods. Where relevant, the results have been interpreted in terms of the basic pinning mechanisms and microstructures in the materials tested. The implications for joint performance are discussed. Secondly, a novel magnetic method was developed to measure the superconducting performance of joints over an unprecedented range of operational conditions. The method involves winding a very small NbTi coil, closing the coil with the joint of interest, and testing the sample in a conventional SQUID magnetometer. The current carrying ability of joints can be measured simply from magnetic hysteresis loops, which enabled the performance of a range of joints to be analysed in fine detail and with considerable convenience. Furthermore, owing to the extremely low coil inductance and highly sensitive SQUID magnetometer employed, current decay curves corresponding to voltages as low as 10-14 V could be obtained in very short measurement times of just 20 minutes. Unfortunately, unexpectedly large drift in the background magnetic field was found to dominate in most measurements, but nevertheless the measurements provided an extremely rapid method of proving that the joints are truly superconducting. Suggestions are made as to how the technique could be improved to permit precise measurements of joint Ic(B, T) and V-I curves in the persistent mode regime, which would enable much needed fundamental studies into superconductivity in joints. Finally, the joint testing technique was employed to measure the superconducting performance of soldered, spot welded and cold pressed NbTi joints. The results were analysed along with the raw material superconducting properties and microstructures in the joints, which were obtained by scanning electron microscopy (SEM). This allowed the performancelimiting factors in each joint to be established. As a result of this study, a new soldering/cold pressing method is proposed which may permit direct metal-to-metal bonding between NbTi materials without the need for Pb or harmful chemicals.